Watching women's liberation, 1970 : feminism's pivotal year on the network news - Dow, Bonnie J. (University of Illinois Press, 2014)
In 1970, ABC, CBS, and NBC - the 'Big Three' of the pre-cable television era - discovered the feminist movement. From the famed sit-in at Ladies' Home Journal to multi-part feature stories on the movement's ideas and leaders, nightly news broadcasts covered feminism more than in any year before or since, bringing women's liberation into American homes. In this book, Bonnie J. Dow uses case studies of key media events to delve into the ways national TV news mediated the emergence of feminism's second wave.
Keywords: Women on television.; Feminism on television.; Feminism -- Press coverage -- United States -- History -- 20th century.; Women's rights -- Press coverage -- United States -- History -- 20th century.; Television broadcasting of news -- United States -- History -- 20th century.; Feminism -- United States -- History -- 20th century.; Femmes à la télévision.; Féminisme à la télévision.; Féminisme -- Couverture de presse -- États-Unis -- Histoire -- 20e siècle.; Femmes -- Droits -- Couverture de presse -- États-Unis -- Histoire -- 20e siècle.; Téléjournaux -- États-Unis -- Histoire -- 20e siècle.; Féminisme -- États-Unis -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; PERFORMING ARTS -- Television -- History & Criticism.; Feminism; Feminism on television; Television broadcasting of news; Women on television; United States; Nachrichtensendung; Fernsehsendung; Feminismus; USA; Feminism.; Könsroller på tv.; Tv-sändning -- historia.; Kvinnors rättigheter -- i massmedia.; 1900-1999; Electronic books.; History